Investigation into the technical feasibility of biological treatment of precious metal refining wastewater - Moore, Bronwyn Ann (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
The hydrometallurgical refining of platinum group metals results in large volumes of liquid waste that requires suitable treatment before any disposal can be contemplated. The wastewater streams are characterized by extremes of pH, high inorganic ion content (such as chloride), significant residual metal loads and small amounts of entrained organic compounds. Historically these effluents were housed in evaporation reservoirs, however lack of space and growing water demands have led Anglo Platinum to consider treatment of these effluents. The aim of this study was to investigate whether biological wastewater treatment could produce water suitable for onsite reuse. Bench-scale activated sludge and anaerobic digestion for co-treatment of an acidic refinery waste stream with domestic wastewater were used to give preliminary data. Activated sludge showed better water treatment at lab scale in terms of removal efficiencies of ammonia (approximately 25%, cf. 20% in anaerobic digestion) and COD (70% cf. 43% in digestion) and greater robustness when biomass health was compared. Activated sludge was consequently selected for a pilot plant trial. The pilot plant was operated on-site and performed comparably with the bench-scale system, however challenges in the clarifier design led to losses of biomass and poor effluent quality (suspended solids washout). The pilot plant was unable to alter the pH of the feed, but a two week maturation period resulted in the pH increasing from 5.3 to 7.0. Tests on algal treatment as an alternative or follow-on unit operation to activated sludge showed it not to be a viable process. The activated sludge effluent was assessed for onsite reuse in flotation and it was found that there was no significant difference between its flotation performance and that of the process water currently used, indicating the effluent generated by the biological treatment system can be used successfully for flotation. Flotation is the method whereby minerals refining operations recover minerals of interest from ore through the addition of chemicals and aeration of the ore slurry. Target minerals adhere to the bubbles and can be removed from the process.
Keywords: Sewage -- Purification -- Biological treatment -- South Africa; Sewage -- Purification -- Activated sludge process -- South Africa; Water reuse -- South Africa; Flotation -- South Africa; Platinum mines and mining -- Waste disposal -- South Africa; Platinum mines and mining -- Economic aspects -- South Africa; Mine water -- Environmental aspects -- South Africa; Platinum mines and mining -- Waste minimization -- South Africa